Mandible-derived extracellular vesicles regulate early tooth development in miniature swine via targeting KDM2B - Ye Li; Meng Sun; Yi Ding; Ang Li (International Journal of Oral Science)
Abstract Tissue interactions play a crucial role in tooth development. Notably, extracellular vesicle-mediated interactions between the mandible and tooth germ are considered essential. Here, we revealed that mandible extracellular vesicles could modulate the proliferation and differentiation of dental mesenchymal cells by regulating the histone demethylase KDM2B. Further investigation showed that mandible derived extracellular vesicles could deliver miR-206 to KDM2B, thereby regulating tooth development. An animal study demonstrated that the miR-206/KDM2B pathway affected tooth morphogenesis and mineralization after eight weeks of subcutaneous transplantation in nude mice. In conclusion, this study suggested that the mandible played a critical role in tooth morphogenesis and mineralization, which could be a potential therapeutic target for abnormal tooth development and an alternative model for tooth regeneration.